A Three-Phased Perishable Inventory Simulation Model with Quality Decrease Consideration - Muhammad Faisal Ibrahim; Yunita Siti Mardhiyyah; Ahmad Rusdiansyah; Meidina Kalse Boer; Dana Marsetiya Utama (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
In this article, focus on the simulation of a three-phase perishable product inventory system of a SMEs selling fresh and processed milkfish. This research was conducted to simulate a perishable product inventory system to understand and analyze the problems that occur then propose solutions to fix them. The simulation model was developed with ARENA software, simulation results of the existing condition show that there is 162 kg/month waste in fresh fish, 158 pcs/month in processed product A, and 86 pcs/month in processed product B. A model with a product renewal process mechanism was proposed to overcome this problem, and seven improvement scenarios were developed. The results obtained from the seventh improvement scenario revealed that there was a 100% reduction in fresh fish and processed product B and 94% in processed product A. Besides, there was a saving in need for fresh fish supply of 10 kg/day. In this article, we show how ARENA software can be adopted to simulate inventory system problems effectively. The method in this research can be applied to investigate various supply system scenarios and their consequences before implementing it in a real system.